Development of Jatropha curcas grown under limited amounts of daily water supply - Adriano-Anaya, Lourdes; Becerra-Monzón, Rodolfo; Vázquez-Ovando, Alfredo; Ovando-Medina, Isidro; Salvador-Figueroa, Miguel (Revista de Ciencias Agrícolas, 2023)
Jatropha curcas plant is known for its soil tolerance and ability to thrive in low humidity conditions; however, there is a lack of systematic reports documenting the impact of limited water availability on its growth and development. This work aimed to analyze the development of J. curcas cultivated with daily supplementation of limited amounts of water. Five daily irrigation treatments were established to simulate varying annual rainfall levels: 250, 750, 1250, 1750 mm and 2250 mm. In each treatment, we used 16 seedlings of J. curcas MAP-08. The seedlings were sown in pots containing loam soil substrate mixed with vermicompost (19: 1 weight to weight). After 60 weeks of cultivation, plants receiving irrigation of 2250 mm per year exhibited growth rates 1.28, 1.51, 1.95 and 1.95 times higher, with respective increases in stem diameter of 15.6, 22.2, 41.9% and 47.7%, as well as 1.2, 1.4, 1.8, and 1.8 more leaves compared to those receiving 1750, 1250, 750, and 250 mm. There was no statistical difference in the number of branches (3.86 branches per plant) between the plants of the treatment with irrigation of 2250, 1750 mm and 1250 mm per year or between the plants belonging to the 750 and 250 mm per year (2.90 branches per plant) treatments. The plants of treatments 1750 and 2250 were the only ones that produced flowers. Although J. curcas typically functions as a succulent deciduous bush, with its stem serving to regulate leaf water potential and acting as a shock absorber against soil water potentials, its morphological and reproductive characteristics were recorded to be negatively affected when subjected to reductions of 22, 44, 67% and 89% in water availability compared to the maximum annual level recorded in the work area (2250 mm).